(untitled) (Texas Journal of Medical Science, 2023)
Allergic rhinitis (AR) is a chronic pathological process, the main pathogenetic mechanism of which is inflammation caused by immunoglobulin E (IgE)–an indirect hypersensitivity reaction that develops as a result of allergens entering the nasal mucosa and manifesting sneezing, nasal congestion, itching and nasal discharge of various nature.